The role of the Miombo Woodlands of the Southern Highlands of Tanzania as carbon sinks - P. K. T. Munishi; S. Mringi; D. D. Shirima; S. K. Linda (African Journal of Environmental Economics and Management, 2021)
Inventory and monitoring of existing carbon pools in ecosystems is important for establishment of baselines for Reduced Emissions from Deforestation and Forest Degradation (REDD) as well as understanding the global carbon budget. We used tree dimensions to quantify the carbon pools of two sites in Miombo woodlands of the Southern Highlands of Tanzania. Mean above ground carbon density of the Miombo ecosystem was 19.2t ha-1 . Of the total carbon, 40 and 60% was contributed by stems and branches respectively. Different species contributed differently to carbon stocks in these ecosystems with Brachystegia spiciformis and Julbernardia globiflora contributing the most. The estimated carbon stocks in this ecosystem is within the range observed in dry forests elsewhere though they are in their early stages of regeneration after extensive exploitation pressure. Under proper management there is a tremendous capacity for carbon storage in these Miombo woodlands to mitigate carbon emissions. Since Miombo species tend to invest much in roots an assessment of below ground carbon in roots can add to the carbon storage potential of these ecosystems. Evaluation of the root and soil carbon in these ecosystems is important in determining the full potential of these ecosystems to act as carbon sink.